Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Bpjs Dan Pasien Umum Rumah Sakit Umum Daerah Undata Provinsi Sulawesi Tengah - Rafliadi; Hattab, Syahruddin; Permana Salingkat, Syarif (JPS: Journal of Publicness Studies, 2024)
This study aims to determine the effect of service quality on the satisfaction of BPJS patients and general patients of Undata Regional General Hospital, Central Sulawesi Province. This study uses the theory of 5 dimensions of service quality according to Kotler and Keller (2016: 442), which consists of Tangible (Physical Evidence), Reliability, Responsiveness, Assurance, and Empathy. This research uses a Mix Method Research Design with a Sequential Exploratory approach. The basis of research using the method of observation, nterviews and questionnaires or questionnaires and the types of data n this study are primary data and secondary data. the sample used was 97 respondents. The results showed that Service Quality had an effect on the satisfaction of BPJS patients and general patients at the Undata Regional General Hospital, Central Sulawesi Province with the value of t count> t table 9.809> 2.69) with a significance level <0.05 (0.001 <0.05) so that Ha was accepted and H0. The dominant Service Quality ndicator that affects BPJS and General Patient Satisfaction s Empathy because t has the greatest mean value compared to other variables. Quantitative data s supported by the results of nterviews with several nformants which show that the Quality of Service of Undata Regional General Hospital, Central Sulawesi Province has not gone well on ndicators of Reliability, Responsiveness, Assurance, Empathy, Tangibles, this can be seen from the non-optimal performance of doctors, uncertain service times, lack of response and friendliness of officers n providing services, nadequate facilities and nfrastructure. All forms of this problem need mprovement so that n the future t can run well.